2017
DOI: 10.1021/acs.joc.7b00540
|View full text |Cite
|
Sign up to set email alerts
|

Phosphazene Catalyzed Addition to Electron-Deficient Alkynes: The Importance of Nonlinear Allenyl Intermediates upon Stereoselectivity

Abstract: An ONIOM(QM/MM) study on the mechanism of the Michael addition to triple bonds catalyzed by chiral diiminophosphorane catalysts has been performed to understand the stereoselectivity of the product olefin. Our results are consistent with the experimental enantioselectivity, but more importantly, reveal that the Z vs E preference depends on the influence of the catalyst upon the geometry of the allenyl enolate formed in the addition step. These intermediates show an innate preference for a (Z)-configuration, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 101 publications
(153 reference statements)
1
10
0
1
Order By: Relevance
“…The mechanisms of this transformation and of the related additions were very recently investigated through computational studies. 885…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…The mechanisms of this transformation and of the related additions were very recently investigated through computational studies. 885…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…Theoretical investigation of the catalytic Michael addition of azlactone and 5 H ‐oxazol‐4‐one to methyl propiolate showed that the Z/E diastereoselectivity of the products is also controlled by the relative orientation of the catalyst and the Michael donor. In view of this, we explored a third route also, which involved attack of 1‐methylpiperazine ( 3 a ) on methyl propiolate from the side opposite to the complexing amine molecule (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Having identified the catalyst capable of promoting a 1,4‐selective reaction with rigorous control of stereoselectivity, we turned our attention to search for a catalyst effective for overturning the regiochemical preference to 1,6‐selectivity while conserving a comparable level of stereocontrol, thereby establishing a site‐divergent stereoselective Michael reaction protocol. Toward this end, we used the P ‐spiro chiral triaminoiminophosphorane 2 as a catalyst, considering the unique ability of its conjugate acid 2 ⋅H to recognize both a nucleophile and an electrophile through hydrogen‐bonding interactions, thus providing an unusual mutual orientation in the transition state for the subsequent bond formation ,. Interestingly, the reaction of 3 a with 4 in the presence of the l ‐valine‐derived 2 a in Et 2 O at 0 °C selectively afforded 1,6‐γ‐ Z , E ‐ 5 a ( vi ) in high yield with excellent enantioselectivity (Table , entry 8).…”
Section: Figurementioning
confidence: 99%